Prototype of ultrasonic sensor-based generator fuel monitoring as a generator fuel level measuring device in the Organizing Unit Dr. F.L Tobing Airport - Diriyanti Novalina, Susi; Sukarwoto, Sukarwoto; Wardani, Ivana; Nabiel, Muhammad (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Dr. Ferdinand Lumbantobing Sibolga Airport Management Unit has three generators with different capacities. The first engine has a capacity of 50 KvA, the second engine is 125 KvA, and the third engine, which is a standby engine and connected to an Acos panel, has a capacity of 250 KvA. This 250 KvA generator serves as a backup if the power supply from PLN goes out, to provide electricity for the Terminal, Office, AFL, Power house, and Dr. F.L. Tobing Airport Tower. This airport gets a current supply of 345 KvA from PLN. Generators are widely known for acting as a backup power source when PLN is off, used at various scales, including at airports. Genset is important to maintain the availability of electricity in aviation safety services. However, generator fuel monitoring at UPBU Dr. F.L. Tobing needs to be improved, because currently it only uses an indicator hose without a fuel exhaustion alarm. This can result in the shutdown of the generator set when fuel is low, so it is necessary to check the fuel capacity periodically while operating to avoid interruptions in power supply. The research method used is quantitative method.